Fiscal Sustainability and Competitiveness in Europe and Asia. - Rajan, Ramkishen S. (Palgrave Macmillan, 2014)
This book examines key issues and policy concerns relating to fiscal sustainability and competitiveness in European and Asian economies. In addition to estimating the extent of fiscal capacity or lack thereof for these economies, the authors supplement the empirical analysis with country case studies.